GABAB, not GABAA receptors play a role in cortical postictal refractoriness - Mareš, Pavel; Kubová, Hana (Neuropharmacology, 2015)
Postictal refractoriness may be taken as an expression of lasting activity of inhibitory systems arresting seizures. We tested drugs interfering with GABAergic inhibitory system in pairs of cortical epileptic afterdischarges induced with 1-min interval in rats. Under control conditions the second stimulation failed to elicit an afterdischarge. This postictal refractoriness was not affected by antagonists of GABAA receptors acting at three binding sites (bicuculline, picrotoxin, benzodiazepine inverse agonist Ro 19-4603) as well as by a less specific antagonist pentetrazol. In contrast, antagonist of GABAB receptors CGP35348 partially blocked the refractoriness. Cooperation of different inhibitory systems is probably necessary to abolish postictal refractoriness in neocortex. This article is part of the Special Issue entitled 'GABAergic Signaling in Health and Disease'.
Keywords: Male; Postictal refractoriness; Rats, Wistar; Bicuculline; elektrická stimulace; organofosforové sloučeniny; antagonisté receptorů GABA-B; CGP35348 (PubChem CID 107699); mozková kůra; Pentylentetrazol (PubChem CID 5917); GABA-B Receptor Antagonists; Picrotoxin (PubChem CID 31304); receptory GABA-B; Electric Stimulation; mužské pohlaví; potkani Wistar; Ro 19-4603 (PubChem CID 127382); implantované elektrody; epilepsie; receptory GABA-A; bikukulin; Animals; Electrodes, Implanted; GABA-A Receptor Antagonists; Organophosphorus Compounds; Cortical seizures; Pentylenetetrazole; Azepines; zvířata; Bicuculline (PubChem CID 102037); Rat; Picrotoxin; Receptors, GABA-B; pentylentetrazol; antagonisté receptorů GABA-A; GABA receptors antagonists; Epilepsy; Receptors, GABA-A; azepiny; pikrotoxin; Cerebral Cortex